Penguatan Future Soft Skills Siswa SMA Melalui Pelatihan Interaktif Untuk Meningkatkan Kesiapan Studi Lanjut dan Kerja - Erbin Chandra; Edy Dharma; Sherly Sherly; Herman Herman (Journal of Social Responsibility Projects by Higher Education Forum, 2026)
−High school students face serious challenges during their transition to higher education and the workforce due to limited mastery of non-technical skills (soft skills). The partner's condition indicates that the regular school curriculum predominantly focuses on formal academic achievements, leaving students with insufficient structured preparation in 21st-century skills. This community service activity aims to strengthen high school students' future soft skills, including critical thinking, problem-solving, communication, collaboration, and creativity, to enhance their readiness for career transitions and further study. The implementation method employed interactive participatory training based on active learning and experiential learning, encompassing interactive lectures, ice-breaking sessions, educational games, group discussions, and case simulations. Program effectiveness was evaluated using Kirkpatrick's Level 1 (Reaction) and Level 2 (Learning) models through satisfaction questionnaires and pre-test/post-test assessments administered to 216 participating students. The results demonstrated an exceptionally high level of participant satisfaction, with an average score of 81.89%. Regarding learning outcomes, significant competency improvements were observed across all soft skill indicators. The highest increase occurred in collaboration skills (26.90%), followed by communication skills (26.68%), critical thinking (24.80%), problem-solving (24.07%), and creativity (21.28%). The novelty of this initiative lies in integrating five future skill domains into a single, compact, and quantitatively measurable interactive training module. The contribution of this activity provides an applicable educational intervention model for schools to design sustainable character development and graduate readiness programs.